MENGHULU BERBUDAYA MELAYU, MENGHILIR RIAU BERINTEGRITAS: NILAI ANTI KORUPSI PADA MATA DIKLAT ANTI KORUPSI BPSDM PROVINSI RIAU - Budiman, Amat (Jurnal Pendidikan Guru, 2018)
Mengulu cultured Malay, Riau contribute to integrity is the re-introduction of Riau Malay culture to the wider community. By preserving the Malay culture is the process of making Riau more beritegritas. In the Malay cultural perspective, the value of anti-corruption is taken from the guidance or guidance of Malay peoples life, namely Tunjuk Ajar Melayu. The value of anti-corruption is also listed in the Anti-Corruption Training Center BPSDM Riau Province. All Malay cultural values can be promoted to prevent and reduce corruption in society and government.